2016
DOI: 10.1007/s00405-016-4189-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative fever and bacterial colonization on packing material following endoscopic endonasal surgery

Abstract: Postoperative fever following endoscopic endonasal surgery is a rare occurrence of concern to surgeons. To elucidate preoperative and operative predictors of postoperative fever, we analyzed the characteristics of patients and their perioperative background in association with postoperative fever. A retrospective review of 371 patients who had undergone endoscopic endonasal surgery was conducted. Predictors, including intake of antibiotics, steroids, history of asthma, preoperative nasal bacterial culture, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The operation requires a longer duration, the contact time between the electrosurgical knife and the submucosa is also extended, mechanical injury to the tissue increases. It is suggested that for patients with large specimens or complicated lesion, we should be alert to postoperative fever, intervene and prevent it early [24].…”
Section: Discussionmentioning
confidence: 99%
“…The operation requires a longer duration, the contact time between the electrosurgical knife and the submucosa is also extended, mechanical injury to the tissue increases. It is suggested that for patients with large specimens or complicated lesion, we should be alert to postoperative fever, intervene and prevent it early [24].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of postoperative fever after cardiac surgeries was 43%, after endoscopic endonasal surgeries was 17%, after cervical fusion surgeries was 25%, and after retrograde internal surgeries was 17.5%. [3][4][5][6] Fever is also a common complication of craniotomy procedures. After craniotomy procedures, the reported incidences of fever were 8.9% to 81.7%.…”
Section: Introductionmentioning
confidence: 99%